Faculty development programs for implementing competency based medical education in India: challenges and opportunities - Nagaraja, Manjunatha S.; M. L., Revathi Devi (International Journal Of Community Medicine And Public Health, 2021)
India has rolled out competency based medical education which means a thorough overhaul of pedagogical and assessment methods. Several new components are introduced which require focussed faculty training and handholding at times. The erstwhile medical council of India had prepared a meticulous roadmap for this and dedicated faculty development programs were initiated for the smooth and effective transition into CBME. The possible challenges and gaps in faculty development are discussed with available options in this paper. To discharge their duties efficiently, the competencies for the faculty also need to be defined and they should progress from ‘knows’ level to ‘does’ level through longitudinal faculty development programs. The fidelity testing is the key for transfer of learning during FDP for the benefit of the students.